As plataformas digitais para profissionais qualificados independentes e seus impactos na Gestão Estratégica de RH (GERH) - Pereira Filho, João Lins (2020)
This study is located in the field of Strategic Human Resources Management (SHRM) and it addresses recent changes in the labor market which tend to influence its evolution. The SHRM research has demonstrated, since its origin, the importance of people management and has indicated sets of HR practices associated with superior organizational performance. However, the growth of the contingent workforce and flexible work models have added new questions and perspectives to the research field. Thus, the objective of this study is to analyze these new working arrangements and their impact on people management, focusing on digital work platforms directed to qualified professionals (freelancers). In order to achieve this goal, the case of a digital platform in Brazil which connects independent contractors in the management area (consultants, advisors, specialists, etc.) with companies from different sectors was analyzed. The results reveal that: (1) independent contractors have a diversified profile and their attitudes towards career can be influenced by the reasons that led them to choose this work arrangement and by their professional identity; (2) hiring freelancers via platforms tends to be seen by organizations as a way of complementing competencies, but these professionals are often involved in strategic activities or projects; (3) traditional people management mechanisms to achieve commitment do not apply in the same way to freelancers; (4) new ways of expressing commitment are emerging in a triad of relationships formed by freelancers, digital platforms and contracting companies. Such results contribute to the practice of people management by driving attention to new ways of integrating qualified professionalsin the organization and their respective impacts. For the SHRM theory, the results indicate the need to develop different models to analyze people management in organizations or areas in which the presence of a flexible workforce is significant.